Limits to the usability of iconic memory - Rensink, Ronald A. (Frontiers in Psychology, 2014)
Human vision briefly retains a trace of a stimulus after it disappears. This trace—iconic memory—is often believed to be a surrogate for the original stimulus, a representational structure that can be used as if the original stimulus were still present. To investigate its nature, a flicker-search paradigm was developed that relied upon a full scan (rather than partial report) of its contents. Results show that for visual search it can indeed act as a surrogate, with little cost for alternating between visible and iconic representations. However, the duration over which it can be used depends on the type of task: some tasks can use iconic memory for at least 240 ms, others for only about 190 ms, while others for no more than about 120 ms. The existence of these different limits suggests that iconic memory may have multiple layers, each corresponding to a particular level of the visual hierarchy. In this view, the inability to use a layer of iconic memory may reflect an inability to maintain feedback connections to the corresponding representation.